‘We work in the grey around decision making’; how ‘thematic discretion’ can help understand police decision-making in cases of youth image-based sexual abuse - Dhir, Alishya (Policing and society, 2025)
In this paper, I argue that a new term, ‘thematic discretion’, can help us understand police decision-making in cases of youth image-based sexual abuse (YIBSA). YIBSA can be defined as harmful image-sharing practices amongst young people, inclusive of the non-consensual sharing of private sexual images, upskirting and cyberflashing, alongside other actions. I will be drawing on findings from a doctoral research project investigating YIBSA, which utilised a mixed methods approach, comprising of quantitative analysis of freedom of information requests from 40 police forces in England and Wales, as well as 26 qualitative interviews with police and non-police practitioners, also based within England and Wales. Research findings established that YIBSA is highly complicated, and as a result, police officers utilised discretion at a considerable rate, alongside crafting their own guidelines to direct their decision-making, which is argued to be steeped in sexist and victim-blaming narratives.